Genetic Modifiers of Duchenne Muscular Dystrophy and Dilated Cardiomyopathy. - Andrea Barp; Luca Bello; Luisa Politano; Paola Melacini; Chiara Calore; Angela Polo; Sara Vianello; Gianni Sorarù; Claudio Semplicini; Boris Pantic; Antonella Taglia; Ester Picillo; et al. (PLoS ONE)
Objective Dilated cardiomyopathy (DCM) is a major complication and leading cause of death in Duchenne muscular dystrophy (DMD). DCM onset is variable, suggesting modifier effects of genetic or environmental factors. We aimed to determine if polymorphisms previously associated with age at loss of independent ambulation (LoA) in DMD (rs28357094 in the SPP1 promoter, rs10880 and the VTTT/IAAM haplotype in LTBP4) also modify DCM onset. Methods A multicentric cohort of 178 DMD patients was genotyped by TaqMan assays. We performed a time-to-event analysis of DCM onset, with age as time variable, and finding of left ventricular ejection fraction < 50% and/or end diastolic volume > 70 mL/m2 as event (confirmed by a previous normal exam < 12 months prior); DCM-free patients were censored at the age of last echocardiographic follow-up. Results Patients were followed up to an average age of 15.9 ± 6.7 years. Seventy-one/178 patients developed DCM, and median age at onset was 20.0 years. Glucocorticoid corticosteroid treatment (n = 88 untreated; n = 75 treated; n = 15 unknown) did not have a significant independent effect on DCM onset. Cardiological medications were not administered before DCM onset in this population. We observed trends towards a protective effect of the dominant G allele at SPP1 rs28357094 and recessive T allele at LTBP4 rs10880, which was statistically significant in steroid-treated patients for LTBP4 rs10880 (< 50% T/T patients developing DCM during follow-up [n = 13]; median DCM onset 17.6 years for C/C-C/T, log-rank p = 0.027). Conclusions We report a putative protective effect of DMD genetic modifiers on the development of cardiac complications, that might aid in risk stratification if confirmed in independent cohorts.